A method of manufacturing inorganic mineral paper ropes
Patent Information
- Application Number
- CN202611042627.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-10-20
AI Technical Summary
[0004]为了解决因现有的纸浆成型采用机械拉伸与矿化改性而导致削弱材料性能的问题,本申请提供一种无机矿物纸绳的制造方法
1、由于本申请首先对矿渣棉纤维表面活化接枝氨基,并对废纸屑酶处理暴露羟基后制成纸浆,纸浆与活化矿渣棉纤维共混后经定向冷冻驱动纤维轴向排列,在冰晶未融状态下施加矿化前驱体液使其沿冰晶与纤维界面浓缩,经冷冻干燥形成孔道骨架后浸入矿化反应液,随后绞制成绳后浸入二次矿化液,再经二次定向冷冻和再次干燥,获得力学强度高、负载均匀牢固且内部孔道规整可控的无机矿物纸绳,而制备工艺具有对纤维取向与矿化分布调控精度高、产品批次性能一致性好的优点。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This application relates to the field of resource recycling and high-performance materials technology, and more specifically, it relates to a method for manufacturing an inorganic mineral paper rope. Background Technology
[0002] Inorganic fiber ropes and paper-based ropes are widely used in packaging, binding, building reinforcement, industrial textiles, and environmental protection applications. Among them, paper ropes made from waste paper fibers have become a development direction to replace traditional plastic ropes and natural fiber ropes due to their wide availability of raw materials, biodegradability, and low production costs. Introducing inorganic fibers derived from industrial solid wastes such as slag wool into the paper-based system can significantly improve the flame retardancy, heat resistance, dimensional stability, and weather resistance of the rope. With the addition of mineralization modification processes, the mechanical load-bearing capacity of the material can be further enhanced.
[0003] However, in existing pulp forming processes, fibers are mostly in a random dispersed state. Conventional forming methods cannot achieve the directional and orderly arrangement of fibers along the rope axis. As a result, when the rope is under load, only a small number of fibers with favorable orientations cooperate to bear the load, which limits the improvement of overall mechanical strength. Furthermore, control methods such as mechanical stretching can easily cause structural damage to the fiber body, thus weakening the material performance. On the other hand, during the mineralization modification process, minerals mostly nucleate homogeneously in the solution and randomly deposit on the fiber surface. It is impossible to precisely limit the contact interface area of different fibers. This makes it difficult to form an efficient interface load transfer structure, resulting in insufficient interface bonding strength. It can also easily cause disordered blockage or uneven size of internal channels. At the same time, conventional drying and forming processes have low precision in controlling the internal channel structure, resulting in large dispersion of channel distribution. It is difficult to simultaneously achieve high mechanical strength and good bending flexibility, and it is also difficult to reliably guarantee the performance consistency between product batches. Summary of the Invention
[0004] To address the problem of weakened material properties caused by mechanical stretching and mineralization modification in existing pulp molding processes, this application provides a method for manufacturing inorganic mineral paper rope.
[0005] This application provides a method for manufacturing inorganic mineral paper rope, which adopts the following technical solution: A method for manufacturing inorganic mineral paper rope includes the following steps: S1. First, the slag wool fiber is surface activated, and the waste paper is enzymatically treated. Then, the enzymatically treated waste paper is mixed with water, magnesium oxide, aluminum oxide, silicon dioxide, modified starch and nanocellulose whiskers and stirred evenly to make pulp. S2. The surface-activated slag wool fiber is mixed with the pulp and then injected into a directional freezing mold for unidirectional freezing to obtain a frozen preform. S3. While the frozen green body is in a state where the ice crystals have not melted, a mineralization precursor liquid containing calcium ions and phosphate ions is applied to the surface of the frozen green body to obtain an interfacial concentrated green body. S4. Freeze-dry the interface-concentrated preform to form a fiber skeleton; S5. Immerse the fiber skeleton in a mineralization reaction solution containing calcium ions and phosphate ions to obtain mineralized fiber skeleton strips. S6. The mineralized fiber skeleton strip is twisted into a rope, and then the twisted paper rope is immersed in a secondary mineralization solution with a concentration lower than that of the mineralization reaction solution to obtain a secondary mineralized paper rope. S7. The secondary mineralized paper rope is subjected to secondary directional freezing, and then freeze-dried again to obtain the finished inorganic mineral paper rope.
[0006] By employing the above technical solution, the slag wool fibers are surface-activated before pulp preparation, allowing the amino functional groups grafted onto their surface to serve as heterogeneous nucleation sites for hydroxyapatite in subsequent mineralization steps. Simultaneously, enzyme treatment microfibrils the waste paper surface and exposes more active hydroxyl groups. These hydroxyl groups enhance the dispersion compatibility of plant and mineral fibers in the aqueous phase and provide binding sites for calcium ion coordination in subsequent interfacial mineralization. The modified starch introduced into the pulp has a regulatory effect on inhibiting excessive ice crystal growth under low-temperature conditions, while nanocellulose whiskers act as heterogeneous nucleating agents for ice crystals during directional freezing, guiding ice crystals to preferentially grow along specific directions, synergistically promoting the establishment of fiber alignment with the subsequent paper rope axis within the preform. Prioritizing the arrangement of fibers; during the directional freezing stage, the unidirectional temperature gradient causes ice crystals to grow directionally from bottom to top. The physical pushing effect of the ice crystal front forces the suspended fibers to align along the ice crystal growth direction. The fiber axial orientation established in this way provides a structural basis for the through-holes formed after subsequent freeze-drying, allowing more fibers in the paper rope to cooperate in bearing the load along the bearing direction when under stress; when the mineralization precursor liquid is applied while the ice crystals are still unmelted, the ice crystals inside the preform occupy a three-dimensional volume, and the liquid precursor cannot penetrate into the area filled by the ice crystals. It can only form a liquid film along the interface gap between the ice crystals and the fiber surface. When the water in the liquid film freezes further at low temperature, calcium ions and phosphate ions are displaced and concentrated at the fiber interface. The concentrated region coincides with the location of the amino functional groups introduced by the surface activation treatment, ensuring that the nucleation sites for subsequent mineralization reactions are confined to the fiber interface. After freeze-drying to remove ice crystals, the axially connected channels retained in the fiber skeleton provide low-resistance pathways for the wetting and penetration of the subsequent mineralization reaction solution. The precursor concentrated at the interface is fixed to the fiber surface in solid form, allowing hydroxyapatite to crystallize and grow in situ at the fiber interface under the guidance of the existing precursor during subsequent immersion in the mineralization reaction solution, forming a continuous mineral bridge across the two fiber interfaces. When the mineralized fiber skeleton strips are twisted into ropes, torsion and radial compression cause local elastic deformation and micro-lattice distortion at the fiber overlap points. These stress-activated The region has a lower nucleation energy barrier in the secondary mineralization solution. The secondary mineralization reaction preferentially deposits minerals at the micro-damage points caused by the stranding process, achieving selective repair of defects introduced by the stranding process. Moreover, when the concentration of the secondary mineralization solution is lower than that of the primary mineralization solution, the mineralization reaction rate slows down, allowing the minerals to grow fully in the stress concentration area. During the secondary directional freezing, the fiber axial arrangement established by the primary directional freezing and the hydroxyapatite lattice orientation generated by the primary mineralization together form a dual structural template, guiding the ice crystals in the residual mineralization solution to grow along the same axis. The directional extrusion force generated by the expansion of the ice crystal volume forces the incompletely solidified mineralized gel phase to flow axially and fill the micro-gaps between the fibers. After the second freeze-drying, the internal pores of the paper rope become regular.
[0007] Preferably, in step S1, the surface activation treatment of the slag wool fiber is as follows: immersing the slag wool fiber in a silane coupling agent solution, stirring at 60-80°C for 30-60 minutes, and then washing and drying to obtain activated slag wool fiber with surface-grafted amino functional groups.
[0008] By adopting the above technical solution, after the slag wool fiber is heated and stirred in a silane coupling agent solution, one end of the silane coupling agent molecule forms a covalent bond with the silanol groups on the surface of the slag wool through a hydrolysis-condensation reaction, while the amino functional group at the other end remains on the fiber surface and extends outward, forming an organic molecular layer with reactive amino groups on the fiber surface. This treatment enables the chemically inert slag wool surface to obtain active sites for electrostatic interaction and coordination with calcium ions and phosphate ions in the subsequent mineralization solution. At the same time, after the amino functional group is protonated into ammonium cations in a weakly alkaline environment, it can attract negatively charged phosphate ions, providing chemical positioning for the selective nucleation of hydroxyapatite at the fiber interface. This transforms the mineralization reaction from random nucleation in a homogeneous solution to heterogeneous and controllable nucleation in a specified area on the fiber surface.
[0009] Preferably, in step S1, the enzymatic treatment of waste paper scraps is as follows: the waste paper scraps are prepared into a suspension with deionized water, cellulase is added, the pH is adjusted to 4.5-5.5 with acid, and enzymatic hydrolysis is performed at 45-55°C for 1-2 hours, followed by inactivation by heating; the amount of enzyme added is 0.5%-1.5% of the oven-dry weight of the enzymatically treated waste paper scraps.
[0010] By adopting the above technical solution, under the action of cellulase, the cellulose segments in the non-crystalline region of the fiber surface of waste paper scraps are partially hydrolyzed and peeled off, exposing the microfiber structure covered by hemicellulose and fine fiber fragments on the fiber surface. This increases the specific surface area of the fiber and the number of surface hydroxyl groups. This enzymatic treatment only removes the outermost barrier layer on the fiber surface without damaging the main strength of the fiber. The increased surface hydroxyl groups improve the swelling and dispersion ability of waste paper fibers in aqueous pulp and provide more coordination binding sites for the adsorption and enrichment of calcium ions on the surface of plant fibers during subsequent mineralization. This enables plant fibers and mineral fibers to have symmetrical nucleation capabilities in the interfacial mineralization reaction.
[0011] Preferably, in step S1, the pulp is made from raw materials comprising the following parts by weight: 30-37 parts water, 7-9.5 parts enzyme-treated waste paper scraps, 7-9.5 parts magnesium oxide, 7-9.5 parts aluminum oxide, 15-19 parts silicon dioxide, 20-25 parts modified starch, and 5-10 parts nanocellulose whiskers.
[0012] By adopting the above technical solution, magnesium oxide, aluminum oxide, and silicon dioxide are uniformly dispersed between pulp fibers as inorganic fillers. After being twisted into ropes, they form the inorganic mineral skeleton of the paper rope, giving the paper rope non-flammability and dimensional stability. The amylopectin molecules of modified starch dissolve in the aqueous phase when stirred at room temperature, increasing the viscosity of the pulp and facilitating the uniform suspension of mineral powder between fibers. In the subsequent directional freezing process, the hydrogen bond network formed between starch molecular chains has a steric hindrance effect on the growth of ice crystals, inhibiting the excessive coarsening of ice crystals and avoiding the disruption of fiber arrangement due to excessively large ice crystal size. Due to its nanoscale rod-shaped morphology and abundant hydroxyl groups on the surface, the nanocellulose whiskers not only serve as a thickening component to improve the thixotropy of the pulp and prevent the sedimentation of mineral powder, but also, because the surface structure of the whiskers has a lattice matching relationship with the ice crystal basal plane, serve as a heterogeneous nucleation substrate for ice crystals during the freezing process, reducing the supercooling requirement for ice crystal nucleation and forming more ice crystals with uniform size in the green body, thereby obtaining a fine and uniform pore structure.
[0013] Preferably, in step S2, the directional freezing temperature is -20 to -40°C, and the freezing time is 2 to 4 hours; the bottom of the directional freezing mold is made of a heat-conducting material and is in contact with the cold source, while the sides and top are made of heat-insulating material.
[0014] By adopting the above technical solution, the structure of the mold bottom being in direct contact with the cold source while the sides and top are insulated allows heat to be transferred in a single direction from bottom to top. After the water in the slurry first nucleates and crystallizes at the bottom, the ice crystals grow longitudinally along the defined temperature gradient direction, forming a directional solidification front that advances from bottom to top. As the ice crystals continue to advance, the fibers suspended in the slurry are pushed away from the interior of the ice crystals by the solid-phase repulsive force generated by the growth of the ice crystals, and are forced to align along the ice crystal growth direction in the gaps between adjacent ice crystals. This arrangement driven by physical force does not rely on mechanical stretching or compression and will not cause additional damage to the fibers themselves. The axial fiber arrangement structure established in this step is still retained after the subsequent freeze-drying to remove the ice crystals, becoming a structural template that runs through the entire paper rope manufacturing process.
[0015] Preferably, in step S3, the temperature of the billet is maintained at -10 to -5°C when the mineralization precursor liquid is applied; the mineralization precursor liquid is a mixture of calcium chloride aqueous solution and disodium hydrogen phosphate aqueous solution, with a calcium-to-phosphorus molar ratio of 1.3:1 to 1.6:1 and a pH of 6 to 8; the application method is atomized spraying, and the spraying volume is 5% to 8% of the billet volume.
[0016] By adopting the above technical solution, the temperature of the billet is maintained within the critical temperature range where the ice crystals have not melted. This prevents the sprayed mineralization precursor liquid from melting in large quantities after contacting the frozen billet, thus preserving the complete three-dimensional ice crystal network inside the billet. The atomized spraying method disperses the mineralization precursor liquid into fine droplets that uniformly cover the outer surface of the billet. Under capillary suction, the droplets penetrate inward along the interfacial gap between the fiber and the ice crystal. However, due to the exclusion effect of the volume occupied by the ice crystal, the liquid film is limited to the interfacial region where the ice crystal and the fiber are in contact. At this temperature, the water in the liquid film continues to freeze slowly. Calcium ions and phosphate ions are continuously enriched in the remaining liquid film because they are expelled from the ice crystal lattice during the freezing process. The local concentration increases, forming a micro-environment with high supersaturation. The location of this micro-environment corresponds to the amino functional groups grafted on the fiber surface. This confined concentration process pre-sets the nucleation sites and local high-concentration driving conditions for the subsequent mineralization reaction, enabling hydroxyapatite to initiate crystallization in the designated interfacial region during formal mineralization.
[0017] Preferably, in step S4, the vacuum degree of the freeze-drying is 5 to 15 Pa, and the freeze-drying is as follows: first, the temperature is maintained at -35°C to -45°C for 3 to 5 hours, then the temperature is increased to -5°C to -15°C at a rate of 0.5 to 1.5°C / h and maintained for 10 to 14 hours, and finally the temperature is increased to 15 to 25°C and maintained for 6 to 10 hours.
[0018] By adopting the above technical solution, freeze-drying is carried out under vacuum conditions. Ice crystals directly sublimate from solid to gas and escape in a stage below their eutectic temperature. This process avoids the disturbance of fiber arrangement by the surface tension of liquid water after the ice crystals melt. The fibers retain the arrangement morphology of directional freezing after drying. The first stage of the stepped heating process is maintained at a lower temperature for a longer time, so that ice crystals in different parts of the blank begin to sublimate simultaneously after the temperature is uniform. This avoids the thermal resistance of the dry layer formed by the sublimation of the outer ice crystals due to excessive heating, which hinders the sublimation of the inner ice crystals. The heating rate in the middle stage allows the bound ice in the capillary channels to be gradually removed while maintaining the integrity of the channels. This prevents the channel walls from cracking and collapsing due to a sudden drop in vapor pressure caused by excessively rapid sublimation. The final stage heats up to room temperature to remove residual adsorbed water. The axially connected channels in the fiber skeleton formed after freeze-drying are fully open, providing a low-resistance channel for the wetting of the subsequent mineralization reaction solution and mass transfer. At the same time, the concentrated precursor fixed at the fiber interface does not undergo morphological changes or positional migration during this process.
[0019] Preferably, in step S5, the mineralization reaction solution is an aqueous solution containing calcium chloride and disodium hydrogen phosphate, wherein the concentration of calcium chloride is 0.1–0.2 mol / L, the concentration of disodium hydrogen phosphate is 0.06–0.12 mol / L, and the pH is 6–8; the mineralization reaction temperature is 40–60°C, and the impregnation time is 2–6 h.
[0020] By adopting the above technical solution, after the fiber skeleton is immersed in the mineralization reaction solution, the permeable channels formed by freeze-drying have wettability, and the mineralization solution fills the entire channel system and contacts the fiber surface through capillary action, especially the concentrated precursor micro-regions fixed at the fiber interface. Under heating conditions, the amino functional groups and concentrated precursors at the interface jointly lower the critical energy barrier for heterogeneous nucleation of hydroxyapatite, promoting the preferential crystallization of mineral ions at the interface between the two fibers. As the mineralization reaction proceeds, hydroxyapatite crystals continue to grow between the surfaces of slag wool fibers and waste paper fibers until a continuous crystal bridge spanning the fiber gap is formed. This mineral bridge connects the two fibers at the molecular level through calcium-oxygen-silicon and calcium-oxygen-carbon chemical bonds. At the same time, the nanoscale rough surface of the crystal forms a mechanical interlock with the fiber surface, which improves the load transfer efficiency of the fiber interface compared to physical bonding. Moreover, this mineralization reaction only occurs in the fiber interface region, and the open space of the internal channels of the fiber skeleton is not filled, thus maintaining the flexibility of the paper rope.
[0021] Preferably, in step S6, the pitch ratio of the stranding is 8-12; the concentration of calcium chloride in the secondary mineralization solution is 0.03-0.06 mol / L, the concentration of disodium hydrogen phosphate is 0.02-0.04 mol / L, the pH is 6-8, the temperature is 40-50℃, and the impregnation time is 1-3 h.
[0022] By adopting the above technical solution, during the process of twisting mineralized fiber skeleton strips into ropes, the relative slippage and torsion between adjacent fiber layers cause stress concentration at the fiber overlap points. When the local stress exceeds the elastic limit, the hydroxyapatite lattice formed by the first mineralization undergoes micro-plastic deformation and generates dislocations and microcracks. The surface atoms at these lattice defects have an unsaturated coordination state, and the surface energy is higher than that of the intact crystal plane. When the twisted paper rope is immersed in a secondary mineralization solution with a low concentration, the high surface energy defect areas become preferential nucleation sites. Mineralized ions selectively deposit at the defects and fill the microcracks, achieving in-situ repair of twisting damage. The low concentration condition makes the mineralization reaction rate slower, ensuring that the deposits are concentrated at the defect sites with the highest activity. This secondary mineralization process uses the stress generated by the twisting process itself as a defect localization means, nesting the forming process and the repair process in sequence, so that the twisting operation is transformed into a triggering condition for subsequent selective strengthening.
[0023] Preferably, in step S7, the temperature of the secondary directional freezing is -25 to -35°C; the vacuum degree of the secondary freeze-drying is ≤10Pa, and the drying time is 12 to 24 hours.
[0024] By adopting the above technical solution, the paper rope after secondary mineralization still retains water from the mineralized solution. When unidirectional freezing is performed again, the nucleation and growth of ice crystals are guided by both the axial arrangement structure of the fibers formed by the first directional freezing and the axial orientation of the hydroxyapatite lattice generated by the first mineralization. The matching relationship between the lattice parameters of the ice crystal basal plane and the size of the fiber axis makes the axial growth of ice crystals energy-favorable, and the ice crystals preferentially grow along the paper rope axis. The volume expansion accompanying the growth of ice crystals generates extrusive force in the axial direction, forcing the not-fully-solidified amorphous mineralized gel phase to undergo viscoplastic flow along the submicron gaps between the fibers and fill them, thereby improving the axial continuity of the fiber skeleton. After freeze-drying again, the ice crystals are sublimated and removed. Due to the structural memory effect of the second freezing, the internal pores of the paper rope are aligned with the direction of the first freezing, avoiding the pore disorder caused by multiple freezing, and finally obtaining an inorganic mineral paper rope product with a regular internal structure.
[0025] In summary, this application has the following beneficial effects: 1. This application first activates and grafts amino groups onto the surface of slag wool fibers, and then exposes hydroxyl groups by enzymatic treatment of waste paper scraps to make pulp. After the pulp is blended with activated slag wool fibers, the fibers are axially aligned by directional freezing. A mineralization precursor liquid is applied while the ice crystals are still intact to concentrate the fibers along the interface between the ice crystals and the fibers. After freeze-drying to form a pore skeleton, the fibers are immersed in a mineralization reaction solution. Subsequently, the fibers are twisted into ropes and immersed in a secondary mineralization solution. After a second directional freezing and drying, inorganic mineral paper ropes with high mechanical strength, uniform and firm load-bearing capacity, and regular and controllable internal pores are obtained. The preparation process has the advantages of high precision in controlling fiber orientation and mineralization distribution and good batch-to-batch performance consistency.
[0026] 2. In this application, a silane coupling agent is preferably used to activate the surface of slag wool fibers. This allows one end of the coupling agent molecule to be covalently linked to the silanol groups on the slag wool surface, while the amino group at the other end extends outward. This treatment gives the slag wool surface active sites that interact with calcium ions and phosphate ions. Furthermore, the amino group attracts negatively charged phosphate ions in a weakly alkaline environment, providing chemical positioning for the selective nucleation of hydroxyapatite. This results in improved interfacial bonding strength between inorganic minerals and slag wool fibers, making them less prone to peeling during bending and friction, and enhancing the weather resistance and durability of the paper rope.
[0027] 3. The method of this application inhibits excessively large ice crystals by using the hydrogen bond network between the molecular chains of modified starch in pulp. At the same time, the nanocellulose whiskers, due to their lattice matching relationship, serve as a heterogeneous nucleation substrate to guide the formation of uniformly sized ice crystals. The two work together to regulate the morphology of ice crystals. Combined with the step-by-step temperature control of freeze drying to ensure uniform sublimation of ice crystals and gradual removal of bound ice from capillary channels to maintain channel integrity, the method achieves uniform and controllable ice crystal growth, complete and uniform internal channels of paper rope, avoids structural defects caused by large ice crystals, and ensures the stability of product mechanical properties and mineralization effect.
[0028] 4. In this application, it is further preferred that the fiber skeleton strips after the first mineralization are twisted into ropes and then immersed in a secondary mineralization solution with a concentration lower than that of the first mineralization solution. The twisting causes stress concentration at the fiber overlap points, resulting in dislocations and microcracks in the hydroxyapatite lattice. The surface energy at the lattice defects increases, and in the lower concentration of the mineralization solution, the defect area becomes a preferential nucleation site, allowing mineral ions to selectively deposit and fill the microcracks. At the same time, the low concentration slows down the reaction rate to ensure that the deposition is concentrated on the defect sites with the highest activity. The stress generated by twisting is used as a positioning signal for subsequent strengthening and repair. The microstructural damage introduced during the forming process is sealed in situ, thereby improving the structural integrity of the paper rope after twisting and the reliability of the finished product. Attached Figure Description
[0029] Figure 1 A flowchart illustrating a method for manufacturing an inorganic mineral paper rope as proposed in this application; Figure 2 This is a schematic diagram showing the mechanical property test results of the embodiments and comparative examples proposed in this application; Figure 3 This is a schematic diagram showing the interface debonding critical load test results of the embodiments and comparative examples proposed in this application; Figure 4 This is a schematic diagram showing the moisture absorption and dimensional stability performance test results of the embodiments and comparative examples proposed in this application; Figure 5 This is a schematic diagram showing the test results of the damp heat aging resistance of the embodiments and comparative examples proposed in this application. Detailed Implementation
[0030] The present application will be further described in detail below with reference to the accompanying drawings and embodiments.
[0031] Technical concept: This application discloses a method for manufacturing inorganic mineral paper rope. The method includes the following steps: S1, firstly, surface activation of slag wool fibers and enzymatic treatment of waste paper scraps to produce pulp; S2, freezing the slag wool fibers and pulp together to obtain a frozen preform; S3, applying a mineralization precursor liquid to the frozen preform to obtain an interfacial concentrated preform; S4, freeze-drying the interfacial concentrated preform to form a fiber skeleton; S5, immersing the fiber skeleton in a mineralization reaction solution to obtain mineralized fiber skeleton strips; S6, twisting the mineralized fiber skeleton strips and then immersing them in a secondary mineralization solution to obtain a secondary mineralized paper rope; S7, subjecting the secondary mineralized paper rope to secondary directional freezing to obtain the finished product.
[0032] This application first activates and grafts amino groups onto the surface of slag wool fibers, and then exposes hydroxyl groups by enzymatic treatment of waste paper scraps to produce pulp. The pulp is then blended with activated slag wool fibers and directionally frozen to drive the axial alignment of the fibers. A mineralization precursor liquid is applied while the ice crystals are still intact to concentrate the fibers along the interface between the ice crystals and the fibers. After freeze-drying to form a pore skeleton, the fibers are immersed in a mineralization reaction solution. Subsequently, the fibers are twisted into ropes and immersed in a secondary mineralization solution. After a second directional freeze-drying and a second drying, an inorganic mineral paper rope with high mechanical strength, uniform and firm load-bearing capacity, and regular and controllable internal pores is obtained. The preparation process has the advantages of high precision in controlling fiber orientation and mineralization distribution, and good batch-to-batch performance consistency.
[0033] Example 1: This example provides a method for manufacturing inorganic mineral paper rope, comprising the following steps: S1. First, the slag wool fiber is surface activated, and the waste paper scraps are enzymatically treated. Then, the enzymatically treated waste paper scraps are mixed with water, magnesium oxide, aluminum oxide, silicon dioxide, modified starch and nanocellulose whiskers and stirred evenly to make pulp.
[0034] The surface activation treatment of slag wool fiber is as follows: slag wool fiber is immersed in silane coupling agent solution, stirred at 60°C for 30 min, and then washed and dried to obtain activated slag wool fiber with surface grafted amino functional groups.
[0035] The enzymatic treatment of waste paper scraps is as follows: the waste paper scraps are prepared into a suspension with deionized water, cellulase is added, the pH is adjusted to 4.5 with acid, and enzymatic hydrolysis is carried out at 45℃ for 1 hour, and then the temperature is raised to inactivate the enzyme; the amount of enzyme added is 0.5% of the oven-dry mass of the enzymatically treated waste paper scraps.
[0036] The pulp is made from the following raw materials in parts by weight: 30 parts water, 7 parts enzyme-treated waste paper scraps, 7 parts magnesium oxide, 7 parts aluminum oxide, 15 parts silicon dioxide, 20 parts modified starch, and 5 parts nanocellulose whiskers.
[0037] S2. After the surface-activated slag wool fiber is mixed with pulp, it is injected into a directional freezing mold for unidirectional freezing to obtain a frozen preform.
[0038] The directional freezing temperature is -20℃, and the freezing time is 2 hours. The bottom of the directional freezing mold is made of heat-conducting material and is in contact with the cold source, while the sides and top are made of heat-insulating material.
[0039] S3. While the frozen green body is in a state where the ice crystals have not melted, a mineralization precursor liquid containing calcium ions and phosphate ions is applied to the surface of the frozen green body to obtain an interfacial concentrated green body.
[0040] The temperature of the billet was maintained at -10℃ when the mineralization precursor liquid was applied; the mineralization precursor liquid was a mixture of calcium chloride aqueous solution and disodium hydrogen phosphate aqueous solution, with a calcium-to-phosphorus molar ratio of 1.3:1 and a pH of 6; the application method was atomized spraying, and the spraying volume was 5% of the billet volume.
[0041] S4. Freeze-dry the interface-concentrated preform to form a fiber skeleton.
[0042] The vacuum degree of freeze drying is 5 Pa. The freeze drying process is as follows: first, maintain the temperature at -35℃ for 3 hours, then raise the temperature to -5℃ at a rate of 0.5℃ / h and maintain it for 10 hours, and finally raise the temperature to 15℃ and maintain it for 6 hours.
[0043] S5. Immerse the fiber skeleton in a mineralization reaction solution containing calcium ions and phosphate ions to obtain mineralized fiber skeleton strips.
[0044] The mineralization reaction solution was an aqueous solution containing calcium chloride and disodium hydrogen phosphate, with a calcium chloride concentration of 0.1 mol / L, a disodium hydrogen phosphate concentration of 0.06 mol / L, and a pH of 6; the mineralization reaction temperature was 40℃, and the impregnation time was 2 h.
[0045] S6. The mineralized fiber skeleton strips are twisted into ropes, and then the twisted paper ropes are immersed in a secondary mineralization solution with a concentration lower than that of the mineralization reaction solution to obtain secondary mineralized paper ropes.
[0046] The pitch ratio of the stranding was 8; the concentration of calcium chloride in the secondary mineralization solution was 0.03 mol / L, the concentration of disodium hydrogen phosphate was 0.02 mol / L, the pH was 6, the temperature was 40℃, and the impregnation time was 1 h.
[0047] S7. The secondary mineralized paper rope is subjected to secondary directional freezing, and then freeze-dried again to obtain the finished inorganic mineral paper rope.
[0048] The temperature for the second directional freezing is -25℃; the vacuum degree for the second freeze drying is ≤10Pa, and the drying time is 12h.
[0049] Example 2: This example provides a method for manufacturing inorganic mineral paper rope, comprising the following steps: S1. First, the slag wool fiber is surface activated, and the waste paper scraps are enzymatically treated. Then, the enzymatically treated waste paper scraps are mixed with water, magnesium oxide, aluminum oxide, silicon dioxide, modified starch and nanocellulose whiskers and stirred evenly to make pulp.
[0050] The surface activation treatment of slag wool fiber is as follows: slag wool fiber is immersed in silane coupling agent solution, stirred at 80°C for 60 min, and then washed and dried to obtain activated slag wool fiber with surface grafted amino functional groups.
[0051] The enzymatic treatment of waste paper scraps is as follows: the waste paper scraps are prepared into a suspension with deionized water, cellulase is added, the pH is adjusted to 5.5 with acid, and enzymatic hydrolysis is carried out at 55℃ for 2 hours, and then the temperature is raised to inactivate the enzyme; the amount of enzyme added is 1.5% of the oven-dry weight of the enzymatically treated waste paper scraps.
[0052] The pulp is made from the following raw materials in parts by weight: 37 parts water, 9.5 parts enzyme-treated waste paper scraps, 9.5 parts magnesium oxide, 9.5 parts aluminum oxide, 19 parts silicon dioxide, 25 parts modified starch, and 10 parts nanocellulose whiskers.
[0053] S2. After the surface-activated slag wool fiber is mixed with pulp, it is injected into a directional freezing mold for unidirectional freezing to obtain a frozen preform.
[0054] The directional freezing temperature is -40℃ and the freezing time is 4 hours; the bottom of the directional freezing mold is made of heat-conducting material and is in contact with the cold source, while the sides and top are made of heat-insulating material.
[0055] S3. While the frozen green body is in a state where the ice crystals have not melted, a mineralization precursor liquid containing calcium ions and phosphate ions is applied to the surface of the frozen green body to obtain an interfacial concentrated green body.
[0056] The temperature of the billet was maintained at -5℃ when the mineralization precursor liquid was applied; the mineralization precursor liquid was a mixture of calcium chloride aqueous solution and disodium hydrogen phosphate aqueous solution, with a calcium-to-phosphorus molar ratio of 1.6:1 and a pH of 8; the application method was atomized spraying, and the spraying volume was 8% of the billet volume.
[0057] S4. Freeze-dry the interface-concentrated preform to form a fiber skeleton.
[0058] The vacuum degree of freeze drying is 15 Pa. The freeze drying process is as follows: first, maintain the temperature at -45℃ for 5 hours, then raise the temperature to -15℃ at a rate of 1.5℃ / h and maintain it for 14 hours, and finally raise the temperature to 25℃ and maintain it for 10 hours.
[0059] S5. Immerse the fiber skeleton in a mineralization reaction solution containing calcium ions and phosphate ions to obtain mineralized fiber skeleton strips.
[0060] The mineralization reaction solution was an aqueous solution containing calcium chloride and disodium hydrogen phosphate, with a calcium chloride concentration of 0.2 mol / L, a disodium hydrogen phosphate concentration of 0.12 mol / L, and a pH of 8; the mineralization reaction temperature was 60℃, and the impregnation time was 6 h.
[0061] S6. The mineralized fiber skeleton strips are twisted into ropes, and then the twisted paper ropes are immersed in a secondary mineralization solution with a concentration lower than that of the mineralization reaction solution to obtain secondary mineralized paper ropes.
[0062] The pitch ratio of the stranding was 12; the concentration of calcium chloride in the secondary mineralization solution was 0.06 mol / L, the concentration of disodium hydrogen phosphate was 0.04 mol / L, the pH was 8, the temperature was 50℃, and the impregnation time was 3h.
[0063] S7. The secondary mineralized paper rope is subjected to secondary directional freezing, and then freeze-dried again to obtain the finished inorganic mineral paper rope.
[0064] The temperature for the second directional freezing is -35℃; the vacuum degree for the second freeze drying is ≤10Pa, and the drying time is 24h.
[0065] Example 3: This example provides a method for manufacturing inorganic mineral paper rope, comprising the following steps: S1. First, the slag wool fiber is surface activated, and the waste paper scraps are enzymatically treated. Then, the enzymatically treated waste paper scraps are mixed with water, magnesium oxide, aluminum oxide, silicon dioxide, modified starch and nanocellulose whiskers and stirred evenly to make pulp.
[0066] The surface activation treatment of slag wool fiber is as follows: slag wool fiber is immersed in silane coupling agent solution, stirred at 70°C for 45 minutes, and then washed and dried to obtain activated slag wool fiber with surface grafted amino functional groups.
[0067] The enzymatic treatment of waste paper scraps is as follows: the waste paper scraps are prepared into a suspension with deionized water, cellulase is added, the pH is adjusted to 5.0 with acid, and enzymatic hydrolysis is carried out at 50℃ for 1.5h, and then the temperature is raised to inactivate the enzyme; the amount of enzyme added is 1.0% of the oven-dry weight of the enzymatically treated waste paper scraps.
[0068] The pulp is made from the following raw materials in parts by weight: 33.5 parts water, 8.25 parts enzyme-treated waste paper scraps, 8.25 parts magnesium oxide, 8.25 parts aluminum oxide, 17 parts silicon dioxide, 22.5 parts modified starch, and 7.5 parts nanocellulose whiskers.
[0069] S2. After the surface-activated slag wool fiber is mixed with pulp, it is injected into a directional freezing mold for unidirectional freezing to obtain a frozen preform.
[0070] The directional freezing temperature is -30℃ and the freezing time is 3 hours; the bottom of the directional freezing mold is made of heat-conducting material and is in contact with the cold source, while the sides and top are made of heat-insulating material.
[0071] S3. While the frozen green body is in a state where the ice crystals have not melted, a mineralization precursor liquid containing calcium ions and phosphate ions is applied to the surface of the frozen green body to obtain an interfacial concentrated green body.
[0072] The temperature of the green body was maintained at -7.5℃ when the mineralization precursor liquid was applied. The mineralization precursor liquid was a mixture of calcium chloride aqueous solution and disodium hydrogen phosphate aqueous solution, with a calcium-to-phosphorus molar ratio of 1.45:1 and a pH of 7. The application method was atomized spraying, and the spraying volume was 6.5% of the green body volume.
[0073] S4. Freeze-dry the interface-concentrated preform to form a fiber skeleton.
[0074] The vacuum degree of freeze drying is 10 Pa. The freeze drying process is as follows: first, maintain the temperature at -40℃ for 4 hours, then raise the temperature to -10℃ at a rate of 1.0℃ / h and maintain it for 12 hours, and finally raise the temperature to 20℃ and maintain it for 8 hours.
[0075] S5. Immerse the fiber skeleton in a mineralization reaction solution containing calcium ions and phosphate ions to obtain mineralized fiber skeleton strips.
[0076] The mineralization reaction solution was an aqueous solution containing calcium chloride and disodium hydrogen phosphate, with a calcium chloride concentration of 0.15 mol / L, a disodium hydrogen phosphate concentration of 0.09 mol / L, and a pH of 7; the mineralization reaction temperature was 50℃, and the impregnation time was 4 h.
[0077] S6. The mineralized fiber skeleton strips are twisted into ropes, and then the twisted paper ropes are immersed in a secondary mineralization solution with a concentration lower than that of the mineralization reaction solution to obtain secondary mineralized paper ropes.
[0078] The pitch ratio of the stranding was 10; the concentration of calcium chloride in the secondary mineralization solution was 0.045 mol / L, the concentration of disodium hydrogen phosphate was 0.03 mol / L, the pH was 7, the temperature was 45℃, and the impregnation time was 2 h.
[0079] S7. The secondary mineralized paper rope is subjected to secondary directional freezing, and then freeze-dried again to obtain the finished inorganic mineral paper rope.
[0080] The temperature for the second directional freezing is -30℃; the vacuum degree for the second freeze drying is ≤10Pa, and the drying time is 18h.
[0081] Comparative Example 1: This comparative example refers to the content of Example 1, except that the slag wool fiber is not surface activated in step S1, that is, the operation of immersing the slag wool fiber in the silane coupling agent solution for stirring is omitted. After the slag wool fiber is crushed, it is mixed with the pulp in its original state. The rest of the content is the same as that of Example 1.
[0082] Comparative Example 2: This comparative example refers to the content of Example 1, except that in step S2, directional freezing is replaced by conventional freezing. That is, the surface-activated slag wool fiber is mixed with pulp and then injected into a regular freezing mold. The bottom, sides and top of the mold are all made of heat-conducting materials. The mold is placed in a freezing environment so that the entire blank is cooled and frozen at the same time, rather than being frozen unidirectionally from bottom to top. The rest of the content is the same as in Example 1.
[0083] Comparative Example 3: This comparative example refers to the content of Example 1, except that in step S3, the mineralization precursor liquid is not applied to the surface of the frozen preform, that is, the ice crystal interface confinement concentration operation is omitted. Instead, in step S5, the freeze-dried fiber skeleton is immersed in a mineralization reaction solution containing calcium ions and phosphate ions. The rest of the content is the same as in Example 1.
[0084] Comparative Example 4: This comparative example refers to the content of Example 1, except that in step S4, freeze drying is replaced by conventional hot air drying, that is, the interface concentrated preform is directly placed in a 50°C hot air oven and dried to constant weight, instead of being freeze-dried to remove ice crystals by sublimation. The rest of the content is the same as Example 1.
[0085] Comparative Example 5: This comparative example refers to the content of Example 1, except that the mineralization reaction is not carried out in step S5. That is, the freeze-dried fiber skeleton is directly used for subsequent stranding, and the operation of immersing the fiber skeleton in the mineralization reaction solution containing calcium chloride and disodium hydrogen phosphate is omitted. The rest of the content is the same as Example 1.
[0086] Comparative Example 6: This comparative example refers to the content of Example 1, except that the twisted paper rope in step S6 is not immersed in the secondary mineralization solution. That is, after being twisted into rope, it directly enters step S7 for secondary directional freezing and re-freeze drying, omitting the secondary mineralization impregnation operation. The rest of the content is the same as Example 1.
[0087] Performance testing Sample preparation: Samples were prepared according to the methods described in the examples and comparative examples. After preparation, each sample was placed in a standard environment with a temperature of 23±2℃ and a relative humidity of 50±5% for 24 hours to equilibrate. Then, a paper rope segment with a length of not less than 500 mm was cut from each sample as a test sample. In each performance test, five samples of each group were measured in parallel, and the results were taken as the arithmetic mean.
[0088] Tensile breaking strength testing: The paper rope specimen is clamped at both ends in the upper and lower clamps of a universal testing machine, with a clamp spacing of 200 mm, ensuring no relative slippage of the specimen within the clamps. The testing machine applies an axial tensile load to the specimen at a constant rate of 50 mm per minute until the specimen fractures, and the maximum load value at the moment of fracture is recorded. The tensile breaking strength is calculated by dividing the maximum load by the actual cross-sectional area of the specimen. The testing standard for this item is GB / T8834-2016 "Determination of Physical and Mechanical Properties of Ropes".
[0089] Testing of bending flexibility: The paper rope sample is placed on a series of round bars with decreasing diameters, ranging from 20 mm to 2 mm. One independent sample is taken from each bar of each diameter for testing. During the operation, the paper rope is bent 180 degrees along the surface of the round bar with a finger and held for 3 seconds before being released. The bent area is then observed for any cracks, breaks, or delamination. Bending flexibility is characterized by the ratio of the minimum bending diameter the sample can withstand without any visible damage to the nominal diameter of the paper rope. A smaller ratio indicates better flexibility. The testing standard for this item is GB / T7690.4-2013 "Test Methods for Reinforcing Yarns - Part 4: Determination of Bending Stiffness".
[0090] Testing of the bonding strength of the mineralized layer interface: A micron-sized indenter was used to perform indentation tests on the interface region between slag wool fibers and waste paper fibers in the cross-section of the paper rope. First, each paper rope sample was cured with resin and then cut, ground, and polished perpendicular to the axial direction to prepare a cross-sectional specimen. On the cross-sectional specimen, an area with a clear interface between the slag wool fibers and waste paper fibers was selected as the indentation test point. An indentation load was applied at a constant loading rate and held for a certain time before being unloaded. The displacement difference and load change curves generated on both sides of the interface during the indentation process were recorded. The bonding strength of the mineralized layer at the interface of the two fibers was evaluated by calculating the indentation work and the critical load value for interface debonding. A higher critical load value indicates a stronger interface bond. The testing standards for this item are GB / T25898-2010 "Instrumented Nanoindentation Test Method for Determination of Hardness and Elastic Modulus" and GB / T30704-2014 "Determination of Hardness by Nanoindentation Method for Superhard Abrasives".
[0091] Testing of moisture absorption rate and dimensional stability of paper ropes: Each paper rope sample was first dried in a forced-air oven at 105±2℃ until constant weight, and then weighed for its oven-dry mass. Subsequently, the samples were placed in a constant temperature and humidity chamber at 40℃ and 90% relative humidity for 72 hours. Immediately after removal, the mass after moisture absorption was weighed, and the percentage of the mass difference before and after moisture absorption to the oven-dry mass was calculated to obtain the moisture absorption rate. Simultaneously, an optical projector or digital calipers was used to measure the outer diameter of the paper rope samples in both the dry and moisture-equilibrium states, and the change in the length direction of the samples was recorded in both states to evaluate the degree of dimensional change of the paper rope in a humid environment. The testing standard for this item is GB / T9995-1997 "Determination of Moisture Content and Moisture Regain of Textile Materials - Oven Drying Method". Dimensional change testing references GB / T6529-2008 "Standard Atmospheres for Conditioning and Testing of Textiles" and GB / T8628-2013 "Preparation, Marking and Measurement of Fabric Samples and Garments in Tests for Determination of Dimensional Changes in Textiles".
[0092] Characterization and testing of the regularity of internal pores in paper rope: The pore size distribution of the internal pore structure of the paper rope samples was determined using mercury porosimetry. Each sample was cut to a size suitable for filling the sample chamber of the mercury porosimetry instrument and then placed into the dilatometer. Mercury injection was performed at both the low-pressure and high-pressure stations, and the amount of mercury entering the paper rope samples under different pressures was measured. The equivalent diameter and pore size distribution width of the pores were calculated based on the correlation between pressure and pore size. The regularity of the pores was evaluated by analyzing the peak concentration and half-peak width of the pore size distribution curve. Sharp peaks and concentrated distribution indicate that the internal pore size of the paper rope is uniform and orderly. The testing standard for this item is GB / T21650.1-2008 "Mercury Porosimetry and Gas Adsorption Methods for Determination of Pore Size Distribution and Porosity of Solid Materials - Part 1: Mercury Porosimetry".
[0093] Testing of paper rope's resistance to humid heat aging: Each paper rope sample was placed in a constant temperature and humidity aging chamber at 85℃ and 85% relative humidity for 168 hours. After that, it was removed and equilibrated under standard environmental conditions for 24 hours. Then, the tensile breaking strength of the aged sample was determined according to the method in test procedure 1. The retention rate of the strength after aging and the strength of the unaged sample was calculated. The higher the retention rate, the better the durability of the paper rope in the humid heat environment. The test standards for this test item refer to GB / T2573-2008 "Aging Test Method for Glass Fiber Reinforced Plastics" and GB / T3511-2018 "Weather Resistance of Vulcanized Rubber or Thermoplastic Rubber".
[0094] Table 1: Test Results of Mechanical and Interfacial Bonding Performance Table 2: Results of moisture absorption and dimensional stability tests Table 3: Test Results of Pore Structure and Resistance to Damp Heat Aging Example Conclusion: See appendix Figure 1 - Appendix Figure 5 Based on the technical solutions of each embodiment and comparative example, the following conclusions can be drawn: Based on Examples 1-3 and Comparative Example 1, and in conjunction with Tables 1 and 2, it can be seen that when slag wool fibers are not surface-activated, the fiber surface lacks amino functional groups that can electrostatically interact with calcium and phosphate ions. Hydroxyapatite cannot achieve selective heterogeneous nucleation at the fiber interface, and the mineralization reaction occurs in the solution rather than the fiber interface region in the form of homogeneous precipitation. This results in a lack of chemical bonding and nanoscale mechanical interlocking structure between the two fibers, leading to a decrease in interfacial bonding strength. At the same time, the capillary channels at the interface that are not blocked by minerals provide a path for water penetration, increasing the moisture absorption rate. The beneficial effect of this factor is that surface activation treatment provides chemical localization for interfacial mineralization, enabling selective crystallization growth of minerals at the interface of the two fibers, forming an interfacial bonding structure and blocking the water penetration path along the interface.
[0095] Combining Examples 1-3 and Comparative Example 2 with Tables 1, 2, and 3, it can be seen that conventional freezing methods cause the entire preform to freeze simultaneously at a lower temperature. Ice crystals randomly nucleate and grow disorderly under multi-directional temperature gradients. After being pushed by the ice crystals, the fibers are randomly distributed rather than axially aligned in a single direction. The pores formed after freeze-drying are isotropically distributed rather than axially interconnected. This disordered structure means that only a small portion of the fibers with favorable orientations bear the load when the paper rope is under load, resulting in reduced tensile strength. The disordered pores increase the local stress concentration points when the fibers bend, reducing flexibility. At the same time, the isotropic nature of the pore structure causes uneven distribution of moisture within the pores after moisture absorption, increasing the rate of dimensional change, and the wide pore size distribution leads to an increased half-peak width. The beneficial effect of this factor is that the unidirectional temperature gradient causes the ice crystals to grow directionally from the bottom to the top, driving the fibers to axially align along the ice crystal growth direction and constructing axially interconnected ordered pores, thus achieving consistency in the fiber bearing direction.
[0096] Combining Examples 1-3 and Comparative Example 3 with Tables 1 and 2, it can be seen that when the ice crystal interface confinement concentration operation is omitted, the freeze-dried fiber skeleton is directly immersed in the mineralization reaction solution. The mineralization ions have equal contact opportunities with all parts of the fiber surface in the solution. Hydroxyapatite widely and homogeneously nucleates and grows in the non-interface region of the fiber surface and the inner wall of the pores, rather than being limited to the interface between the two fibers. Due to the lack of pre-placed high-concentration precursor micro-regions at the interface, the mineralization reaction needs to go through a homogeneous induction period before it can start, resulting in insufficient nucleation density and growth of minerals at the interface, and reduced interfacial bonding strength. At the same time, the minerals attached to the inner wall of the pores increase the water adsorption sites and increase the hygroscopic rate. The beneficial effect of this factor is that the physical exclusion effect of the ice crystal occupying the volume confines the mineralization precursor liquid to the interface region between the ice crystal and the fiber and achieves solute concentration, so that the nucleation sites of the subsequent mineralization reaction are fixed at the fiber interface, thus achieving spatial selectivity of interface mineralization.
[0097] Based on Examples 1-3 and Comparative Example 4, and in conjunction with Tables 1, 2, and 3, it can be seen that during conventional hot air drying, after the ice crystals melt in the preform, the liquid water, under the action of surface tension, drags and disturbs the fiber arrangement, destroying the axial fiber arrangement structure established by directional freezing, causing the fibers to rebound, deflect, and agglomerate. The capillary contraction force during the evaporation of liquid water causes the pore wall to collapse, the axially continuous pore structure disappears, and transforms into irregular shrinkage pores. At the same time, the mineralized precursors concentrated at the interface diffuse and are lost from the fiber interface during water flow and migration, and cannot play a positioning and nucleation role in subsequent mineralization. The three factors of disordered fiber arrangement, pore collapse, and precursor loss work together to deteriorate mechanical properties, flexibility, moisture absorption, pore regularity, and aging resistance. The beneficial effect of this factor is that the direct sublimation of ice crystals avoids the destruction of fiber arrangement and pore structure by the surface tension and capillary contraction force of liquid water, maintains the axial orientation and pore integrity of the fiber skeleton, and fixes the interface-concentrated precursors in place to prevent migration and loss.
[0098] Combining Examples 1-3 and Comparative Example 5 with Table 1, it can be seen that in the fiber skeleton without the first mineralization reaction, the two fibers only rely on physical entanglement and mechanical compression during twisting to contact each other. There is a lack of chemical bonding and mineral bridging structure across the interface, and the load cannot be transferred through the interface. The tensile strength comes only from the frictional resistance and physical entanglement of the fiber itself. After the fiber skeleton strips are twisted into ropes, there is a lack of anchoring effect of minerals between the layers, and the critical load for interface debonding is reduced. The beneficial effect of this factor is that the hydroxyapatite crystals grown in situ at the interface bridge the interface of the two fibers, realize chemical bonding at the molecular level and form mechanical interlocking at the nanoscale, and provide a load transfer path for the paper rope.
[0099] As can be seen from Examples 1-3 and Comparative Example 6, and Tables 1 and 3, in paper ropes that have not undergone secondary mineralization after being twisted into ropes, micro-cracks and lattice dislocations caused by twisting are retained inside the product, becoming the starting point for stress concentration and crack propagation during subsequent use. At the same time, in a humid and hot environment, moisture preferentially penetrates these defective areas, accelerating interface deterioration. Although the lattice formed by the first mineralization produces dislocations under the twisting stress, it is not repaired, resulting in insufficient load-bearing capacity and reduced durability of the paper rope during subsequent use. The beneficial effect of this factor is that it utilizes the twisting stress to activate lattice defects, making them high-energy nucleation sites, and guides the selective deposition of minerals in the damaged area in the secondary mineralization liquid, realizing the in-situ sealing and repair of defects introduced by twisting, and transforming the forming stress into a driving force for subsequent strengthening.
[0100] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A method for manufacturing inorganic mineral paper rope, characterized in that, Includes the following steps: S1. First, the slag wool fiber is surface activated, and the waste paper is enzymatically treated. Then, the enzymatically treated waste paper is mixed with water, magnesium oxide, aluminum oxide, silicon dioxide, modified starch and nanocellulose whiskers and stirred evenly to make pulp. S2. The surface-activated slag wool fiber is mixed with the pulp and then injected into a directional freezing mold for unidirectional freezing to obtain a frozen preform. S3. While the frozen green body is in a state where the ice crystals have not melted, a mineralization precursor liquid containing calcium ions and phosphate ions is applied to the surface of the frozen green body to obtain an interfacial concentrated green body. S4. Freeze-dry the interface-concentrated preform to form a fiber skeleton; S5. Immerse the fiber skeleton in a mineralization reaction solution containing calcium ions and phosphate ions to obtain mineralized fiber skeleton strips. S6. Twist the mineralized fiber skeleton strip into a rope, and then immerse the twisted paper rope in a secondary mineralization solution with a concentration lower than that of the mineralization reaction solution to obtain a secondary mineralized paper rope. S7. The secondary mineralized paper rope is subjected to secondary directional freezing, and then freeze-dried again to obtain the finished inorganic mineral paper rope.
2. The method for manufacturing an inorganic mineral paper rope according to claim 1, characterized in that, In step S1, the surface activation treatment of the slag wool fiber is as follows: the slag wool fiber is immersed in a silane coupling agent solution and stirred at 60-80°C for 30-60 minutes. After washing and drying, activated slag wool fiber with amino functional groups grafted on the surface is obtained.
3. The method for manufacturing an inorganic mineral paper rope according to claim 1, characterized in that, In step S1, the enzymatic treatment of waste paper scraps is as follows: the waste paper scraps are prepared into a suspension with deionized water, cellulase is added, the pH is adjusted to 4.5-5.5 with acid, and enzymatic hydrolysis is performed at 45-55℃ for 1-2 hours, followed by inactivation by heating; the amount of enzyme added is 0.5%-1.5% of the oven-dry mass of the enzymatically treated waste paper scraps.
4. The method for manufacturing an inorganic mineral paper rope according to claim 1, characterized in that, In step S1, the pulp is made from raw materials comprising the following parts by weight: 30-37 parts water, 7-9.5 parts enzyme-treated waste paper scraps, 7-9.5 parts magnesium oxide, 7-9.5 parts aluminum oxide, 15-19 parts silicon dioxide, 20-25 parts modified starch, and 5-10 parts nanocellulose whiskers.
5. The method for manufacturing an inorganic mineral paper rope according to claim 1, characterized in that, In step S2, the directional freezing temperature is -20 to -40°C, and the freezing time is 2 to 4 hours; the bottom of the directional freezing mold is made of a heat-conducting material and is in contact with the cold source, while the sides and top are made of an insulating material.
6. The method for manufacturing an inorganic mineral paper rope according to claim 1, characterized in that, In step S3, the temperature of the billet is maintained at -10 to -5°C when the mineralization precursor liquid is applied; the mineralization precursor liquid is a mixture of calcium chloride aqueous solution and disodium hydrogen phosphate aqueous solution, with a calcium-to-phosphorus molar ratio of 1.3:1 to 1.6:1 and a pH of 6 to 8; the application method is atomized spraying, and the spraying volume is 5% to 8% of the billet volume.
7. The method for manufacturing an inorganic mineral paper rope according to claim 1, characterized in that, In step S4, the vacuum degree of the freeze-drying is 5 to 15 Pa, and the freeze-drying is as follows: first, maintain the temperature at -35℃ to -45℃ for 3 to 5 hours, then raise the temperature to -5℃ to -15℃ at a rate of 0.5 to 1.5℃ / h and maintain it for 10 to 14 hours, and finally raise the temperature to 15 to 25℃ and maintain it for 6 to 10 hours.
8. The method for manufacturing an inorganic mineral paper rope according to claim 1, characterized in that, In step S5, the mineralization reaction solution is an aqueous solution containing calcium chloride and disodium hydrogen phosphate, wherein the concentration of calcium chloride is 0.1–0.2 mol / L, the concentration of disodium hydrogen phosphate is 0.06–0.12 mol / L, and the pH is 6–8; the mineralization reaction temperature is 40–60℃, and the impregnation time is 2–6 h.
9. The method for manufacturing an inorganic mineral paper rope according to claim 1, characterized in that, In step S6, the pitch ratio of the stranding is 8-12; the concentration of calcium chloride in the secondary mineralization solution is 0.03-0.06 mol / L, the concentration of disodium hydrogen phosphate is 0.02-0.04 mol / L, the pH is 6-8, the temperature is 40-50℃, and the impregnation time is 1-3 h.
10. The method for manufacturing an inorganic mineral paper rope according to claim 1, characterized in that, In step S7, the temperature of the secondary directional freezing is -25 to -35°C; the vacuum degree of the secondary freeze drying is ≤10Pa, and the drying time is 12 to 24 hours.